2021
DOI: 10.3389/fsufs.2021.614348
|View full text |Cite
|
Sign up to set email alerts
|

Toward Specialized or Integrated Systems in Northwest Europe: On-Farm Eco-Efficiency of Dairy Farming in Germany

Abstract: Intensive confinement (IC) systems for dairying have become widespread during the last decades. However, potential advantages of alternative systems such as full-grazing (FG) or integrated dairy/cash-crop (IFG) systems with regards to better provision of ecosystem services are widely discussed. To investigate performance and environmental impacts, we compared four prevailing dairy systems using an on-farm research study. The farm types differed in their share of pasture access and quantity of resource inputs: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 100 publications
2
17
0
Order By: Relevance
“…The results also show that milk yield is positive and statistically significant, supporting the finding of Ali, et al [45] that dairy farms adopting improved genetic materials attain higher productivity. Our analysis also shows stocking density as positive and significant, consistent with Reinsch, Loza, Malisch, Vogeler, Kluß, Loges and Taube [22] and Kimura and Sauer [1], finding that dairy farms operating intensive systems tend to be relatively more productive. The intensity of the purchased feed input variable is negative and significant after controlling for other factors (note that, contrary to the results of the econometric analysis, the productivity class analysis based on mean comparison shows that high-productivity farms use more purchased feeds.…”
Section: Regression Analysis Of Farm-level Productivitysupporting
confidence: 87%
See 1 more Smart Citation
“…The results also show that milk yield is positive and statistically significant, supporting the finding of Ali, et al [45] that dairy farms adopting improved genetic materials attain higher productivity. Our analysis also shows stocking density as positive and significant, consistent with Reinsch, Loza, Malisch, Vogeler, Kluß, Loges and Taube [22] and Kimura and Sauer [1], finding that dairy farms operating intensive systems tend to be relatively more productive. The intensity of the purchased feed input variable is negative and significant after controlling for other factors (note that, contrary to the results of the econometric analysis, the productivity class analysis based on mean comparison shows that high-productivity farms use more purchased feeds.…”
Section: Regression Analysis Of Farm-level Productivitysupporting
confidence: 87%
“…Intensity of the production system exhibits a more complex relationship. While intensity (stocking density) is related to relatively higher productivity [1,19,21,22], the intensity of purchased feed and labour input use is negative [1,23], indicating that efficiency is still a key driver, regardless of structural advantages.…”
Section: Review Of Empirical Studiesmentioning
confidence: 99%
“…This is often realised by high inputs of nitrogen (N) fertiliser. Nonetheless, nitrogen use efficiency in dairy production systems is low [4][5][6] and high N inputs are a key factor for N surpluses and N leaching losses under permanent pastures [3,7]. Grass swards with higher plant N uptake showed significantly lower N leaching losses [7].…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted by Nyameasem et al [34], on the same experimental site, reported low levels of N 2 O emissions which further indicates the effective use of N in the low-input system [20]. With regard to the N on a farm-level, a low-input ley-systems based on grazing allows for high productivity in combination with high biodiversity effects [68], low GHG emissions [16,34] and milk production with a low carbon footprint, thereby resulting in eco-efficient dairy systems [69]. These low-input systems could therefore serve as a platform in order to reduce the negative environmental effects associated with dairy farming in northern Germany which will adhere to the European Union Nitrate Directive [8], the Water Framework Directive [9] and the Groundwater Directive [10], organizations that aim to protect both surface and groundwater from agricultural use.…”
Section: Field-n-balancementioning
confidence: 86%